Enhancing Salted Fish Product Value to Empower Producer Groups in Kertajaya Village, a Coastal Community of Sumur, Pandeglang, Banten Province - Silalahi, Ronald Maraden Parlindungan; Nugraha Ranudinata, Hari; Kristanto, Desi Dwi; Mantofani, Rizal (Sebatik, 2025)
The community service program implemented in Kertajaya Village, Sumur Subdistrict, Pandeglang Regency, Banten Province, aims to enhance the market value and competitiveness of salted fish products, which constitute one of the primary economic commodities of this coastal community. The majority of residents depend on fisheries and seafood processing for their livelihoods; however, production activities still rely heavily on traditional sun drying techniques that are vulnerable to weather variability. This condition leads to inconsistent product quality, unstable production capacity, and limited access to broader markets. To address these challenges, the program introduces a series of structured capacity building activities targeted at youth organizations (karang taruna) and local salted fish processors. The training focuses on processing innovations, improved hygiene practices, modern packaging design, branding strategies, microenterprise management, and the utilization of digital marketing platforms. A participatory and inclusive approach is adopted to ensure that community members are actively involved in planning, implementing, and sustaining the activities, thereby shifting their role from passive beneficiaries to empowered local entrepreneurs. The initiative is expected to stimulate the growth of creative and competitive coastal business actors, increase household income, and strengthen the village’s identity as a center for value added salted fish production. Furthermore, the program provides a replicable model for community empowerment rooted in local potential, economic resilience, and environmental sustainability in coastal regions.